Beyond abundance and biomass: Effects of marine protected areas on the demography of a highly exploited reef fish - Taylor, B.; McIlwain, Jennifer (Inter-Research, 2010)
The success of marine protected areas (MPAs) in facilitating recovery of over-exploited stocks has been well documented. Few studies, however, have explored the effects of MPAs on the demographic profiles of reef fish populations. We tested the assumption that areas closed to fishing for >7 yr accumulate older individuals of a heavily targeted species, Lethrinus harak. Our survey design included 2 protected sites and 2 comparative fished sites. Using an age-based lengthconversion method, a novel approach in tropical fisheries, otolith-derived demographic information was supplemented with underwater visual census data. This approach provided valuable insights into the population dynamics of this species at small spatial scales (<2 km2). We found considerable site-specific differences in the age structure of L. harak, with protected sites having greater mean ages and lower total mortality. There was indication of density-dependent growth as greater size-at-age occurred in fished sites where biomass had been depleted. Although female L. harak reach 50% maturity at 208 mm fork length (FL) or age 3.8 yr, it is the largest and oldest females (>260 mm FL and >9 yr) who make a disproportionate contribution to overall reproductive output, as ovary weight increases exponentially with both length and age. Currently size (Lc) and age (tc) at first capture is ~100 mm and 2 yr below the size (L50) and age (t50) at first maturity. Numerous management scenarios based on minimum size limits were evaluated to determine which scenario would increase spawning biomass without compromising yield estimates. Our results demonstrate that effective implementation of MPAs allows a larger and older population to accrue, thus yielding considerable reproductive benefits.